2013
DOI: 10.1159/000351671
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Addenbrooke's Cognitive Examination III in Frontotemporal Dementia and Alzheimer's Disease

Abstract: Background/Aims: The aims of this study were to validate the newly developed version of theAddenbrooke's Cognitive Examination (ACE-III) against standardised neuropsychological tests and its predecessor (ACE-R) in early dementia. Methods: A total of 61 patients with dementia (frontotemporal dementia, FTD, n = 33, and Alzheimer's disease, AD, n = 28) and 25 controls were included in the study. Results: ACE-IIIcognitive domains correlated significantly with standardised neuropsychological tests used in the asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
710
4
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 757 publications
(743 citation statements)
references
References 62 publications
14
710
4
15
Order By: Relevance
“…As one of the purposes of defining core measures is to make individual studies comparable and meta-analysable, it would be helpful for a future study to formulate an algorithm to be able to compare scores on both the ADAS-Cog and the MMSE and to consider developing algorithms specifically for individual subtypes of dementia. This has recently been accomplished for the ACE-3 (Addenbrooke's Cognitive Examination -third edition) 471 and the MMSE (Professor Gill Livingston, University College London, 4 April 2016, personal communication). This should be possible as a recently published study of the longitudinal cognitive decline of mild to moderate AD participants in placebo arms of 20 trials found the trajectories of the ADAS-Cog and MMSE to be similar.…”
Section: Core Domainsmentioning
confidence: 99%
“…As one of the purposes of defining core measures is to make individual studies comparable and meta-analysable, it would be helpful for a future study to formulate an algorithm to be able to compare scores on both the ADAS-Cog and the MMSE and to consider developing algorithms specifically for individual subtypes of dementia. This has recently been accomplished for the ACE-3 (Addenbrooke's Cognitive Examination -third edition) 471 and the MMSE (Professor Gill Livingston, University College London, 4 April 2016, personal communication). This should be possible as a recently published study of the longitudinal cognitive decline of mild to moderate AD participants in placebo arms of 20 trials found the trajectories of the ADAS-Cog and MMSE to be similar.…”
Section: Core Domainsmentioning
confidence: 99%
“…45 The more comprehensive Addenbrooke's Cognitive Examination III, originally designed as a global screening tool for dementia, tests naming by also asking patients to name 12 pictures. 46 The Boston Naming Test, designed specifically to assess naming by picture confrontation, is a tool widely used by clinicians, as it is easy to administer and score. 47 Initial information gathered about naming performance from these sources (i.e., subjective reports, clinical impression, performance on screening/naming tests) can help the clinician in narrowing the differential diagnoses before requesting further tests, which may include blood chemistry, neuroimaging, neurophysiology, or specialized neuropsychological tests.…”
Section: Clinical Approach To Naming Impairmentsmentioning
confidence: 99%
“…The comparison group comprised a convenience sample of 55 people aged over 65 who by self-report were healthy with no subjective memory problems or a diagnosis of dementia. Where comparison group participants scored below the threshold score of 82 on the ACE-III (where dementia is detected with 100% specificity, (Hsieh et al 2013)), their data were excluded from analysis. The sample was recruited by advertisement in community groups and snowball sampling.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…It is a widely used and acceptable measure for people with dementia and is frequently used as a screening tool within memory services. It has been validated against its predecessor the ACE-R and other standardised tests of neuropsychological functioning in early dementia (Hsieh et al 2013), and has been shown to have high internal reliability (Cronbach's α = 0.88 (Velayudhan et al 2014)). …”
Section: Addenbrooke's Cognitive Examination-iiimentioning
confidence: 99%